Consulting report – T-Copia S.A. - Arroyo, Carlos; Loloy, Silvana (Pontificia Universidad Católica del Perú, 2017)
T-Copia is a Peruvian company with more than 40 years of trajectory, they started providing printing services in their retail stores, and years later, with the technological changes in the industry, they created its second business unit: Digital Solutions. Currently they continue with this two business units, but is one of them which is facing some issues. After reviewing the financial information and interviewing some of the employees of the company, many problems were detected, overall in the first business unit, reason why the whole project is focused in this one. The key problem in here was that during this year only six of the seven stores have achieved the profitability. After analyzing the company not only in a quantitative way, but also in a qualitative one, the conclusion was that the decrease in the sales was produced overall for the lack of training and motivation in the staff, which leaded to a poor customer service. Therefore, the proposed solutions were focused in the improvement of these two fields. Regarding the training it is important to complement the soft skills like team-work or emotional intelligence whit hard skills, given that the company’ services are very particular and require a previous knowledge to provide an accurate customer service. About the motivation, two fields have to be approached; the first one is the extrinsic, which is going to be solved by the company with the regularization of the payments to the staff. The second one is the intrinsic motivation, which is going to be addressed by the Doctrine of 20%, focused on the employees with more potential and commitment, by letting them use the 20% of their working time in innovative projects to save cost or increase the sales of the company. The propose solutions will take in consideration the financial situation of the company, and they will represent no big investment of money, because there will be an exchange of services with other companies

T-Copia es una empresa peruana con más de 40 años de trayectoria. En sus inicios proveía únicamente servicios de impresión en sus tiendas minoristas, pero años más tarde, con los cambios tecnológicos en la industria, vieron la necesidad de crear su segunda unidad de negocios: Soluciones Digitales. Actualmente continúan con estas dos unidades de negocio. Tras revisar la información financiera y entrevistar a varios de los empleados de la empresa, se detectaron distintos problemas, principalmente en la cadena de tiendas minoristas, razón por la cual el proyecto se centrará en éste. El problema principal es la falta de rentabilidad en siete de sus trece tiendas. Después de analizar la empresa no sólo de manera cuantitativa, sino cualitativa también, se llegó a la conclusión de que la disminución en las ventas se debe mayormente a la falta de formación y motivación del personal, lo que conduce a un deficiente nivel de servicio al cliente. Por lo tanto, las soluciones propuestas se centraron en la mejora de estos dos campos. En cuanto a la formación, es importante complementar las habilidades blandas, como el trabajo en equipo o la inteligencia emocional, con el conocimiento técnico en los trabajadores, dado que los servicios de la empresa requieren un conocimiento técnico para poder proporcionar una adecuada asesoría a los clientes. En cuanto a la motivación, se abordan dos campos; el primero es la motivación extrínseca, que va a ser resuelta por la empresa con la regularización de los pagos al personal; y el segundo es la motivación intrínseca, que va a ser abordada por la Doctrina del 20%, la cual se centra en los empleados con más potencial y compromiso, permitiéndoles utilizar parte de su tiempo de trabajo en proyectos innovadores para la empresa. Las soluciones propuestas toman en cuenta la situación financiera de la empresa, y no representaran una gran inversión, debido a que se hará un intercambio de servicios con otras empresas
Keywords: Empresas -- Organización; Administración de empresas; Servicios al cliente; https://purl.org/pe-repo/ocde/ford#5.02.04